The Influence of Enterprise Risk Management Implementation on Financial Performance and Firm Value in East Asia - Natasha, Tiurma; Rokhim, Rofikoh (Dinasti Publisher, 2024)
Risk management is critical for businesses since every organization is accountable for delivering value to stakeholders and developing corporate strategy through management decisions at all levels. As a result, a comprehensive strategy to risk management is required . A solid and effective risk management and internal control system must be implemented in conjunction with good corporate governance. Implementing effective and well-managed risk management will help company to reach the goals, increase the performance, and produce better work. The study examines the impact of Enterprise Risk Management on the financial performance and firm value of selected listed firms in East Asia for the period 2018 to 2022. This research was conducted using data from the Financial Statements of 151 companies that meet the specific criteria and are listed on the Exchange of five East Asian countries. The data was collected from 2018 through 2022. The Multiple Linear Regression model was employed. The research findings suggest that the financial performance of a corporation is positively correlated with the implementation of Enterprise Risk Management.